Risk factors for gametocyte carriage in Gambian children. - Lorenz von Seidlein; Chris Drakeley; Brian Greenwood; Gijs Walraven; Geoffrey Targett (2001)
A widespread reduction in Plasmodium falciparum gametocyte prevalence could reduce malaria transmission. After infection with P. falciparum, a variable proportion of people are found to be gametocytemic. We analyzed risk factors associated with gametocytemia at presentation and 7 days later. We enrolled 1,198 children in 2 antimalarial drug trials between September and December 1998. The children were assigned to 1 of 4 treatment groups: chloroquine only; pyrimethamine-sulfadoxine (PSD) only; PSD combined with 1 dose of artesunate; and PSD combined with 3 doses of artesunate. By the time of enrollment, 200 (17%) of 1,198 children were gametocyte carriers. Three independent risk factors were associated with gametocytemia at enrollment. Children with anemia were more likely to carry gametocytes, whereas children with fever (> 37.4 degrees C) or high parasite densities (> 100,000 parasites/microL) were less frequently gametocyte carriers. Children with at least 2 of the risk factors were 4 times more likely to be gametocytemic than children with < 2 risk factors (odds ratio [OR], 4.4; 95% confidence interval [CI], 2.7-7.1). Seven days after the start of treatment, 355 (37%) of 466 assessable children were found to be gametocyte carriers. Children treated with PSD alone had a significantly higher risk of being gametocytemic by Day 7 compared with children in the other 3 treatment groups. In the subgroup of children who had no detectable gametocytes on enrollment, the effect of treatment with PSD + 3 doses of artesunate was most marked. Nineteen (10%) of 198 children treated with PSD + 3 doses of artesunate became gametocytemic, in contrast to 184 (57%) of 321 children treated with PSD alone (OR, 12.7; 95% CI, 7.3-22.1). Early treatment with highly effective antimalarial therapy has the greatest chance of preventing gametocytemia. The choice of a first-line antimalarial drug for uncomplicated malaria should not only take into consideration the ablation asexual parasitemia but also the suppression of gametocytemia.